Asymptomatic Plasmodium infection and glycemic control in adults: Results from a population-based survey in south-central Côte d'Ivoire. (October 2019) - Eze, Ikenna C.; Essé, Clémence; Bassa, Fidèle K.; Koné, Siaka; Acka, Félix; Schindler, Christian; Imboden, Medea; Laubhouet-Koffi, Véronique; Kouassi, Dinard; N'Goran, Eliézer K.; Utzinger, Jürg; Bonfoh, Bassirou; et al.
Highlights: We studied the association between Plasmodium infection (PI) and glycemic control. Glycemic control markers were fasting glucose (FG) and glycated hemoglobin (HbA1c). FG-based prediabetes and diabetes were higher than HbA1c-based diagnoses. Asymptomatic PI was independently associated with FG, but not with HbA1c. FG-based diabetes diagnosis in a background of PI may overestimate diabetes burden. Abstract: AIMS: We investigated the cross-sectional associations of Plasmodium infection (PI) with fasting glucose (FG) and glycated hemoglobin (HbA1c) in malaria-endemic south-central Côte d'Ivoire. Methods: We studied 979 participants (non-pregnant; no treated diabetes; 51% males; 18–87 years) of the Côte d'Ivoire Dual Burden of Disease study. Fasting venous blood was obtained for PI, FG, and HbA1c assessment. We defined PI as a positive malaria rapid diagnostic test (RDT) or microscopic identification of Plasmodium species. We applied multivariable linear regressions to assess beta coefficients (β) and 95% confidence intervals (CIs) of PI positivity for FG and HbA1c independent of diabetes risk factors. Results: Prevalence of PI was 10.1% (5.5% microscopy; 9.7% RDT) without clinical fever. Prevalence of FG-based prediabetes (45.8%) and diabetes (3.6%) were considerably higher than HbA1c-based values (2.7% and 0.7%, respectively). PI was independently associated with FG among participants with higher body temperature (β 0.34, 95% CI 0.06–0.63, pheterogeneity  = 0.028), or family history of diabetes (β 0.88, 95% CI 0.28–1.47, pheterogeneity  = 0.009). Similar patterns observed with HbA1c were obliterated on accounting for FG. We also observed consistent associations with parasite density. Conclusions: FG-based diabetes diagnosis in the presence of asymptomatic PI may misclassify or overestimate diabetes burden in malaria-endemic settings. Longitudinal studies are needed to confirm these findings and determine the risk for diabetes.